Possibilities of establishing a ‘small-scale geopark’: examples from the area of Upper Zemplín (Slovakia) // Możliwość utworzenia małych geoparków: przykłady z obszaru Gór Zemplińskich (Słowacja) - Baláž, Bartolomej; Štrba, Ľubomír (Geotourism/Geoturystyka, 2017)
Within relatively new forms of tourism, geotourism takes a well-established position and is developing worldwide. Hand in hand with the development of geotourism, a demand for defining different types of attractive geotourist locations or regions has arisen. Besides typical geotourist locations (geosites) and regions (geoparks), there are several areas that are geo-attractive and cover several individual geosites, but are too small to be defined as “classical” geoparks. This paper discusses an alternative approach to geotourist development by defining ‘smallscale’ geoparks through the example of the eastern part of Slovakia, near the border with Ukraine. The area is characterized by (1) a variegated geological structure, which includes five main geological units of the Carpathians in Slovakia, where many different-type geosites are located (e.g. mineralogical, hydrogeological, volcanological, paleontological, etc.), (2) presence of historical monuments (e.g. castle ruins), (3) botanical objects and (4) wine-producing areas. // Pośród względnie nowych form turystyki geoturystyka zajmuje ugruntowaną pozycję i rozwija się na całym świecie. Jednocześnie z rozwojem geoturystyki pojawiło się zapotrzebowanie na różne rodzaje atrakcyjnych lokalizacji lub regionów geoturystycznych. Poza typowymi obiektami i obszarami geoturystycznymi (geoparki) istnieje kilka atrakcyjnych obszarów, które są zbyt małe, by mogły być uznane za geoparki. Niniejszy artykuł przedstawia alternatywne podejście do zagospodarowania geoturystycznego w postaci „małych geoparków” na przykładzie wschodniej części Słowacji, przy granicy z Ukrainą. Obszar ten charakteryzuje się: (1) zróżnicowaną budową geologiczną, na którą składa się pięć głównych jednostek strukturalnych Karpat Słowackich, charakteryzujących się zróżnicowanymi obiektami geoturystycznymi (mineralogicznymi, hydrogeologicznymi, wulkanologicznymi, paleontologicznymi, etc.), (2) obecnością zabytków historycznych (np. ruin zamków), (3) obecnością obiektów przyrody ożywionej (roślinność) i (4) obecnością winnic.